2019
DOI: 10.1002/dmrr.3138
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects and safety of Roux‐en‐Y gastric bypass surgery vs. conventional medication in obese Chinese patients with type 2 diabetes

Abstract: Aim: To assess metabolic effects and safety of Roux-en-Y gastric bypass (RYGB) versus conventional medication (CM) in obese Chinese patients with type 2 diabetes (T2DM).Methods: This retrospective cohort study included 40 patients who underwent RYGB (mean age 44.1 years, body mass index [BMI] 33.3 kg/m 2 ) and 36 patients administered CM (mean age 49.4 years, BMI 32.1 kg/m 2 ). The primary endpoint was achievement of the triple endpoint (haemoglobin A1C [HbA1c] < 7.0%, lowdensity lipoprotein cholesterol < 2.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 40 publications
8
37
0
1
Order By: Relevance
“…To best of our knowledge, the present study is the largest cohort study that evaluated the effectiveness of bariatric surgery among Chinese population using population-based data. [15][16][17][38][39][40] The results of this study were in line with the conclusion of previous observational studies and randomised controlled trials (RCTs), which found that bariatric surgery provided substantial and sustainable effects on weight loss, glycaemic control, and lipid profile improvement. 15,42,[44][45][46] However, observations of the present study were at variance with other studies regarding to diabetes remission and weight loss in quantitative aspect and hypertension remission from qualitative perspective.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To best of our knowledge, the present study is the largest cohort study that evaluated the effectiveness of bariatric surgery among Chinese population using population-based data. [15][16][17][38][39][40] The results of this study were in line with the conclusion of previous observational studies and randomised controlled trials (RCTs), which found that bariatric surgery provided substantial and sustainable effects on weight loss, glycaemic control, and lipid profile improvement. 15,42,[44][45][46] However, observations of the present study were at variance with other studies regarding to diabetes remission and weight loss in quantitative aspect and hypertension remission from qualitative perspective.…”
Section: Discussionsupporting
confidence: 90%
“…To best of our knowledge, the present study is the largest cohort study that evaluated the effectiveness of bariatric surgery among Chinese population using population‐based data . Also, this study made a comprehensive illustration of metabolic and weight outcomes, including complete and partial remission rates of diabetes, remission rates of hypertension, high LDL‐C, low HDL‐C, high triglycerides and dyslipidaemia, and improvement of BMI, HbA 1c , SBP, DBP, LDL‐C, %TWL, %EWL, and %REWL.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The initial search resulted in 231 papers. After duplication removal and application of inclusion and exclusion criteria, 16 articles [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were included in the qualitative analysis. The flowchart of the research strategy is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Decreases in HbA1c and fasting blood glucose levels were also noticed and reached normal levels at 1-3 months after surgery. Complete NAFLD remission was achieved in 96% of post-RYGB patients as well as diabetes remission in 48% of post-RYGB patients, thereby improving cardiovascular risk factors [42].…”
Section: Impact Of Gastric Bypass Surgery On Gut Microbiotamentioning
confidence: 99%